Indirect Selection of Tolerant Barley (Hordeum vulgare L.) Genotypes under Semi Arid Conditions Based on the Numerical Images Analysis Indices - Ali Guendouz; Ramdane Benniou; Hocine Bendada; Nasreddine Louahdi (Université de M'sila, 2021)
Image analysis systems have been increasingly utilized for the assessment of plant growth and health for decades. We used in this study the software Mesurim Pro to evaluate the variation of the leaf reflectance at Red, Green and Blue and the variation of the senescence parameters. The analysis of variance revealed that the reflectance at different wavelengths (Red, Blue and Green) was highly significant genotypes effects (P < 0.001); for this parameter the good genotypes are those we have the lowest values such as G19. In addition, the preferable genotypes were those which have low values for the mean senescence and senescence velocity; based on this raison the best genotype was the introduce genotype G12. The genotypes effect was significant for the grain yield and thousand-kernel weight, for the chlorophyll content and the analysis of variance showed a significant effect of genotypes, the highest values registered by the introduced genotype G5 this one was in the same homogenize group of G2, G4, G8 and G18. The ranking of genotypes based on all parameters suggested that the genotypes G11, G12, G5, G15 and G18, respectively (introduce genotypes) were the ideal genotypes under these conditions
Keywords: Barley (Hordeum vulgare L.), Reflectance, Senescence, Selection, Semi-arid.